Software Ecosystems, Sustainability and Human Values in the Social Web : 8th Workshop of Human-Computer Interaction Aspects to the Social Web, WAIHCWS 2017, Joinville, Brazil, October 23, 2017 and 9th Workshop, WAIHCWS 2018, Belém, Brazil, October 22, 2018, Revised Selected Papers /: 8th Workshop of Human-Computer Interaction Aspects to the Social Web, WAIHCWS 2017, Joinville, Brazil, October 23, 2017 and 9th Workshop, WAIHCWS 2018, Belém, Brazil, October 22, 2018, Revised Selected Papers. (2020) - Unknown
No abstract available